2017
DOI: 10.3762/bjnano.8.219
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of low-energy dissociative electron attachment in Fe(CO)5 upon clustering

Abstract: In this work, we probe anion production upon electron interaction with Fe(CO)5 clusters using two complementary cluster-beam setups. We have identified two mechanisms that lead to synthesis of complex anions with mixed Fe/CO composition. These two mechanisms are operative in distinct electron energy ranges. It is shown that the elementary decomposition mechanism that has received perhaps the most attention in recent years (i.e., dissociative electron attachment at energies close to 0 eV) becomes suppressed upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 23 publications
4
34
0
Order By: Relevance
“…Low energy electron interaction with gas phase clusters of Fe(CO) 5 have also be conducted, representing a step closer to FEBID by including intermolecular interactions. DEA processes involving pure Fe(CO) 5 clusters, and Fe(CO) 5 /Ar clusters 13,18 again identified Fe(CO) 4…”
Section: ■ Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Low energy electron interaction with gas phase clusters of Fe(CO) 5 have also be conducted, representing a step closer to FEBID by including intermolecular interactions. DEA processes involving pure Fe(CO) 5 clusters, and Fe(CO) 5 /Ar clusters 13,18 again identified Fe(CO) 4…”
Section: ■ Introductionmentioning
confidence: 83%
“…− as the primary product, although its intensity was lower than observed for the isolated gas phase studies, suggesting that DEA is suppressed by intermolecular interactions. 13 In contrast to the isolated gas phase studies, ions containing two and three iron atoms were identified. The synthesis of these more complex heteronuclear anions was attributed to self-scavenging, 18 where anions attach to monomer units.…”
Section: ■ Introductionmentioning
confidence: 92%
“…Still, as is illustrated in figure 8, the mass resolution is high enough to determine the branching ratios between the three fragments reliably. The spectrum is cumulative 41,42 -it has been obtained as a sum of the mass spectra in the energy range 3 to 8 eV. The dashed lines show the individual contributions of the three close-lying fragments and the full red line shows their sum.…”
Section: Dissociative Electron Attachmentmentioning
confidence: 99%
“…Fe(CO) 5 is one of the most common FEBID precursors used to fabricate magnetic nanostructures for magnetic sensing, spintronics, and magnetologic technologies [23,[30][31][32][33][34]. Apart from that, a large number of gas-phase and surface science experiments have been performed over the last years to study the electron-induced dissociation mechanisms for isolated Fe(CO) 5 molecules [35][36][37], those embedded in a cluster environment [38][39][40][41], and condensed on a surface in the form of Fe(CO) 5 thin films [42,43].…”
Section: Introductionmentioning
confidence: 99%